Disminución de barreras arquitectónicas del espacio público en escenarios deportivos de la ciudad de Cali (2015)
This article aims to highlight the research process addressed by the students of sixth semester of the program of Architectural Drawing and Decoration of Academia de Dibujo Profesional and the results of architectural and urban projects that seek to reduce architectural barriers of public space in sports venues in the city of Cali. It will initially show the research methodology applied as an academic exercise at the institution, then to reflect on the achievements obtained both in the research field and as a function of the design solutions that meet accessibility criteria in urban spaces.